The mother-child realtionship: an analysis according to the psychoanalytical theory - Farias, Cynthia Nunes de Freitas; Lima, Glaucineia Gomes de (Clinical Styles. The Journal on the vicissitudes of childhood, 2004)
The aim of this paper is to analyze the statute of the mother-child relationship, according to the psychoanalytical theory. The authors discuss both the Freudian concepts, which link the maternity to the castration and postulate that the son is a substitute for the phallus, and the post-Freudian publications, which state that the son represents an answer to the femininity. The authors also report the concepts of Lacan regarding the maternity and the castration as a separating factor between the mother and the woman.